Kilka refleksji na temat specyfiki i problemów postępowania rekrutacyjnego do samorządowych przedszkoli i szkół - Lisowski, Piotr (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
The judgment of the Polish Constitutional Court of 8 January 2013 K 38/12, OTK-A 2013, nr 1, poz. 1 necessitated changes in the legislation on the principles and procedures of recruitment in preschools and schools including the establishments maintained by selfgovernment units. However, neither the amendment of the Act on Education nor the provisions of the Law on Education take into account the legal-administrative insights into – establishment-administration specific – forms of activities of public administration which finalise this type of recruitment proceedings. The paper studies the causes of this situation, at the same time analysing educational regulations and the judicial adjudication which accompanies their application. The resultant conclusions and remarks culminate in the call for an appropriate amendment of current regulations.
Keywords: recruitment; administrative decision; administrative establishment